Jon ran 21km (7+14 because robert ran 14 less so you add the 14 additional km to jon’s total)
So, h(t) is how far is Daniel's head from the surface of the water, namely the surface itself is when the height is nill, so his head is at the surface and the height of it is just 0, thus h(t) = 0. Namely, what is "t" when h(t) is 0?
![\bf h(t)=-8t^2-28t+60\implies \stackrel{h(t)}{0}=-8t^2-28t+60 \\\\\\ 0=-2t^2-7t+15\implies 2t^2+7t-15=0\implies (2t+3)(t-5)=0 \\\\\\ \begin{cases} 2t+3=0\implies 2t=-3\implies &t=-\frac{3}{2}\\\\ t-5=0\implies &\boxed{t=5} \end{cases}](https://tex.z-dn.net/?f=%5Cbf%20h%28t%29%3D-8t%5E2-28t%2B60%5Cimplies%20%5Cstackrel%7Bh%28t%29%7D%7B0%7D%3D-8t%5E2-28t%2B60%0A%5C%5C%5C%5C%5C%5C%0A0%3D-2t%5E2-7t%2B15%5Cimplies%202t%5E2%2B7t-15%3D0%5Cimplies%20%282t%2B3%29%28t-5%29%3D0%0A%5C%5C%5C%5C%5C%5C%0A%5Cbegin%7Bcases%7D%0A2t%2B3%3D0%5Cimplies%202t%3D-3%5Cimplies%20%26t%3D-%5Cfrac%7B3%7D%7B2%7D%5C%5C%5C%5C%0At-5%3D0%5Cimplies%20%26%5Cboxed%7Bt%3D5%7D%0A%5Cend%7Bcases%7D)
clearly the seconds cannot be a negative unit, so is not -3/2.
Answer:
9.95 for 30oz
Step-by-step explanation:
30/9.95 = 3.02
12/3.5 = 3.43
Answer:
P = -0.004Q + 149
Step-by-step explanation:
The general form of the linear equation is:
![P=aQ+b](https://tex.z-dn.net/?f=P%3DaQ%2Bb)
The slope of the equation (a) can be found by using the two given points (4,000; $133) and (27,000; $41)
![a = \frac{\$41-\$133}{27,000-4,000}\\a=-0.004](https://tex.z-dn.net/?f=a%20%3D%20%5Cfrac%7B%5C%2441-%5C%24133%7D%7B27%2C000-4%2C000%7D%5C%5Ca%3D-0.004)
Applying the point (4,000; $133) to the equation below yields in the linear equation for Price as a function of the number of shirts:
![P-P_0=a(Q-Q_0)\\P-133=-0.004(Q-4,000)\\P = -0.004Q+149](https://tex.z-dn.net/?f=P-P_0%3Da%28Q-Q_0%29%5C%5CP-133%3D-0.004%28Q-4%2C000%29%5C%5CP%20%3D%20-0.004Q%2B149)
The linear equation is:
P = -0.004Q + 149
Step-by-step explanation:
In the recursive formula an = an−1 + 5
![a_n = a_{n-1}+5](https://tex.z-dn.net/?f=a_n%20%3D%20a_%7Bn-1%7D%2B5)
Suppose if a_5 is the nth term then previous term is a_4
To get the previous term we need to subtract 1 from the n
So a_n is the nth term
is the previous term
Here 5 represents the common difference between two terms
So value of previous term is represented by
![a_{n-1}](https://tex.z-dn.net/?f=a_%7Bn-1%7D)
Answer : ![a_{n-1}](https://tex.z-dn.net/?f=a_%7Bn-1%7D)